Serogroup B Protein Meningococcal Vaccines and the Formation of Immune Protection against Gonorrhea - N. N. Kostyukova; V. A. Bekhalo (Эпидемиология и вакцинопрофилактика)
Relevance. Gonorrhea is a widespread infection. More than 80 million cases of this disease occur annually. The problem is compounded by the growing resistance of gonococcus to antibiotics worldwide. The only way out in this situation may be the immunization of certain groups of the population against this infection. Despite the numerous efforts of specialists, there is currently no registered vaccine against gonorrhea, which is due to the characteristics of the pathogen. However, over the past 30 years, reliable observations have accumulated that vaccines containing N. meningititidis serogroup B outer membrane proteins (OMP), developed for prophylaxis meningococcal infection, can also prevent a significant proportion of gonorrhea cases. Aims. To give a brief overview of publications on the reduction of the incidence of gonorrhea in individuals who received vaccines containing N. meningitidis serogroup B outer membrane vesicles, followed by an analysis of information about the nature of these proteins and methods of their study, as a promising platform for creating a vaccine against gonococcus. Conclusions. There is a theoretical and real possibility of creating a preventive drug against gonorrhea. Our analysis of literature sources showed that during the period 2006–2016 from 31% to 59% of those vaccinated with the protein meningococcal vaccine В were protected from gonorrhea. It is necessary to continue studying meningococcal OMV in terms of their preventive properties against gonorrhea, improve the set of models to identify their protective effect, and find adjuvants that enhance the immunogenicity of potential vaccine candidates.